2010
DOI: 10.1128/jvi.01693-09
|View full text |Cite
|
Sign up to set email alerts
|

Human Rhinovirus 14 Enters Rhabdomyosarcoma Cells Expressing ICAM-1 by a Clathrin-, Caveolin-, and Flotillin-Independent Pathway

Abstract: Intercellular adhesion molecule 1 (ICAM-1) mediates binding and entry of major group human rhinoviruses (HRVs). Whereas the entry pathway of minor group HRVs has been studied in detail and is comparatively well understood, the pathway taken by major group HRVs is largely unknown. Use of immunofluorescence microscopy, colocalization with specific endocytic markers, dominant negative mutants, and pharmacological inhibitors allowed us to demonstrate that the major group virus HRV14 enters rhabdomyosarcoma cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 50 publications
1
29
1
Order By: Relevance
“…In addition to atherosclerosis, adhesion molecules such as ICAM-1 are also implicated in the progression of infection (35)(36)(37). A recent study reported that manganese blocks intracellular trafficking of Shiga toxin and that manganese-supplemented mice were completely resistant to a lethal Shiga toxin challenge (38).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to atherosclerosis, adhesion molecules such as ICAM-1 are also implicated in the progression of infection (35)(36)(37). A recent study reported that manganese blocks intracellular trafficking of Shiga toxin and that manganese-supplemented mice were completely resistant to a lethal Shiga toxin challenge (38).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the cellular requirements, we can now include Ebola virus, adenovirus 35 (Ad35), influenza A virus (IAV), Kaposi's sarcoma-associated herpesvirus (KSHV), vaccinia virus extracellular virions (VV EVs), vaccinia virus mature virions of the IHD-J strain (VV MV IHD-J), and Nipah virus to the growing list of viruses using macropinocytosis [10 ,12,14 ,16 ,32,45 ,48-52]. While more research is required, bluetongue virus 1 (BTV-1), and human Rhinoviruses 8 and 14 (HRV8 and HRV14) may be tentatively included [53][54][55]. Human papillomavirus-16 (HPV-16) has been included to exemplify macropinocytic-like virus entry.…”
Section: Kinases Gtpases and Other Factorsmentioning
confidence: 99%
“…Macropinocytosis of HIV-1 (in macrophages), human rhinovirus-14 (HRV-14), and bluetongue virus-1 (BTV-1) was inhibited by dynasore, and entry of human rhinovirus-8 (HRV-8) by dynasore and the dynamin-2 dominant negative [53][54][55]67]. Although not required for lamellopodia-associated and bleb-associated macropinocytosis [13,52,74], dynamin-2 is needed for closure of PDGF-stimulated circular ruffles [53,67,75,76].…”
Section: Kinases Gtpases and Other Factorsmentioning
confidence: 99%
“…HRV14 binding triggers internalisation of virusreceptor complexes presumably via clathrin and caveolin independent endocytosis. At least in rhabdomyosarcoma cells overexpressing ICAM-1 this process is actin dependent and blocked by the Na þ /H þ -exchange inhibitor amiloride but unaffected by dominant negative mutants of amphiphysin and AP-180 [78]. Shortly after internalisation, the virus localises to early endosomal antigen 1 (EEA1)-labelled early endosomes that receive cargo incoming via distinct entry routes for subsequent intracellular sorting (Figure 2).…”
Section: Major Group Human Rhinoviruses Entry and Intracellular Traffmentioning
confidence: 99%